Uji Kadar Albumin dan Pertumbuhan Ikan Gabus (Channa striata) dengan Kadar Protein Pakan Komersial yang Berbeda [Albumin Level Test and Snakehead Fish (Channa striata) Growth with Different Commercial Feed Protein Level] - Moch. Amin Alamsjah; Galuh Ajeng Kusumaningrum; Endang Dwi Masithah (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Gabus fish is rich of albumin. This fish as albumin source for hypoalbumin (lower albumin) patients and wound, both post operation wound and burn. Albumin have many sulfhydrile compound (SH) have a function as radikal bind. Protein which have rich of –SH compound be able to binding hazard metal and also antioxidant effects and salic acid. At present, albumin produced from human blood, then the price is expensive enough. The finding of albumin extract from gabus fish then become alternative to get cheap albumin. This research purposed to recognize about the influence by providing different protein feed on albumin level and the growth of gabus fish. Method that used in this research is experimental method, with Complete Random Design as trial design. Treatment that given such different protein level included, Po treatment with 26% protein, P1 treatment with 29% protein, P2 treatment with 32% protein respective repeated six times. The main parameter that observed are albumin and growth of Gabus fish. Supporting parameter that observed in this research are temperature measurement, pH and DO, Variant Analysis (ANOVA) and to know about Duncan Multiple Range test treatment. The result of the research indicates that found different albumin level on Gabus fish is not real among treatment above on observation yields. The highest average of albumin level found in P2 treatment, while lowest influence taken from treatments of P0 and P1. The growth of Gabus fish with providing commercial feed with different protein level indicates that found different growth of real Gabus fish (p< 0,05). The highest yield taken from P2 treatment is really different with other treatments. While lowest yield taken from P0 and P2 treatment.